COMPUTING RELIABILITY FOR CLOSED-CYCLE COOLING SYSTEM IN THERMO-ELECTRIC POWER PLANTS BY MODELLING TO CIRCULAR CONSECUTIVE-2-OUT-OF-n:F SYSTEM - Gurcan, Mehmet; Gokdere, Gokhan (Vinca Inst Nuclear Sci, 2018)
The main motivation of this paper is to compute a reliability for a closed recurring water supply system with n water pumps in a thermo-electric plant by modelling to a repairable circular consecutive-2-out-of-n:F system. In a thermo-electric plant system, let us have n water pumps for pumping the water and steam expelled from a turbine to a cooling tower. These pumps are installed around the system and each pump must be powerful enough to pump water and steam to at least the next two consecutive pumps. If any two or more consecutive pumps in the system are failed, the system is failed. For this system, it is important to determine the reliability. First, we developed mathematical formulations for the state transition probabilities in the system by using the definition of generalized transition probability and the concept of critical component under the assumption that pumps have unequal failure rates. Then, using these formulations we derived the state transition probability matrix of the system. Finally, a special model is given to calculate the system reliability.
Keywords: closed-cycle cooling system; circular consecutive-2-out-of-n:F repairable system; reliability; generalized transition probability; critical component